PENGARUH KETERLIBATAN ORANG TUA TERHADAP PRESTASI AKADEMIK SISWA DI SMPN 56 JAKARTA - Permatasari, Intan; kartika, Putri; Masrohah, Siti; Samian; Yanto, Sri (UNIVERSITAS SERAMBI MEKKAH, 2024)
This study aims to examine the influence of parental involvement on the academic achievement of students at SMPN 56 Jakarta. The research method used is quantitative with a survey design. Data were collected through questionnaires given to 150 students in grades VII and VIII and their parents. The variable of parental involvement was measured through several indicators, including support in home study, participation in school activities, and communication between parents and teachers. The academic achievement of students was measured based on the latest semester report card grades. Regression analysis results show that parental involvement has a positive and significant influence on students' academic achievement (β = 0.45, p < 0.05). Parental support in home study and effective communication between parents and teachers are the most dominant factors in improving students' academic achievement. Parental participation in school activities also contributes, although not as much as the other two factors. This study concludes that parental involvement is an essential factor in enhancing students' academic achievement. Therefore, schools and related parties need to encourage and facilitate parental involvement in their children's education process. This effort can be made through programs that strengthen communication and cooperation between schools and families.